Polarization dependent beaming properties of a plasmonic lattice laser - Benjamin O Asamoah; Henri Partanen; Sughra Mohamed; Janne Heikkinen; Atri Halder; Matias Koivurova; Marek Nečada; Tero Setälä; Jari Turunen; Ari T Friberg; Tommi K Hakala (New Journal of Physics, 2021)
We study beaming properties of laser light produced by a plasmonic lattice overlaid with organic fluorescent molecules. The crossover from spontaneous emission regime to stimulated emission regime is observed in response to increasing pump fluence. This transition is accompanied by a strong reduction of beam divergence and emission linewidth due to increased degree of spatial and temporal coherence, respectively. The feedback for the lasing signal is shown to be mainly one-dimensional due to the dipolar nature of the surface lattice resonance. Consequently, the beaming properties along x and y directions are drastically different. From the measurements, we obtain the M ^2 value along both principal directions of the square lattice as a function of the pump fluence. Our work provides the first detailed analysis of the beam quality in plasmonic lattice lasers and reveals the underlying physical origin of the observed strong polarization dependent asymmetry of the lasing signal.